2021
DOI: 10.1371/journal.pone.0258302
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature and mental health hospitalizations in Bern, Switzerland: A 45-year time-series study

Abstract: Background Psychiatric disorders constitute a major public health concern that are associated with substantial health and socioeconomic burden. Psychiatric patients may be more vulnerable to high temperatures, which under current climate change projections will most likely increase the burden of this public health concern. Objective This study investigated the short-term association between ambient temperature and mental health hospitalizations in Bern, Switzerland. Methods Daily hospitalizations for menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 70 publications
7
28
0
Order By: Relevance
“…Finally, with obsession-compulsion, interpersonal sensitivity, phobic anxiety, and paranoid ideation, further psychopathological entities were connected to foehn's winds. Of note is paranoid ideation, since patients with psychotic symptoms appear to be particularly vulnerable to the influence of environmental factors [17], and so often need hospitalization in situations with symptom exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, with obsession-compulsion, interpersonal sensitivity, phobic anxiety, and paranoid ideation, further psychopathological entities were connected to foehn's winds. Of note is paranoid ideation, since patients with psychotic symptoms appear to be particularly vulnerable to the influence of environmental factors [17], and so often need hospitalization in situations with symptom exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies find that temperature affects the prevalence of depression and sadness: the prevalence of depression is highest in summer and autumn ( 48 ). Psychiatric patients may be more vulnerable to high temperatures ( 23 ), which under current climate change projections will most likely increase the concerns of people in poor mental states. Bundo et al ( 23 ) find that increasing temperatures could negatively affect mental status in psychiatric patients using a 45-year time-series study.…”
Section: Further Studymentioning
confidence: 99%
“…Psychiatric patients may be more vulnerable to high temperatures ( 23 ), which under current climate change projections will most likely increase the concerns of people in poor mental states. Bundo et al ( 23 ) find that increasing temperatures could negatively affect mental status in psychiatric patients using a 45-year time-series study. Thus, compared with normal people, patients with depression are more likely to do something to protect themselves from climate risks.…”
Section: Further Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In Switzerland, Bundo and colleagues [ 17 ] showed that the hospitalization risk for mental disorders increased linearly by 4.0% for every 10 °C increase in mean daily temperature in a 45-year study period. Higher risks have been identified in patients with developmental disorders and schizophrenia.…”
Section: Introductionmentioning
confidence: 99%